PENGARUH CITRA MEREK, KUALITAS PELAYANAN, DAN HARGA TERHADAP KEPUTUSAN PENGGUNAAN JASA GO-JEK DI ITC BSD. - Panji Nugroho, - (2019)
This research is a quantitative research that aims to determine the effect of brand image, service quality, and price on the decision to use Go-Jek services. The population in this study were Go-Jek service users at ITC BSD. The sample size was taken as many as 75 respondents, with non probability sampling method, especially purposive sampling. Data collection is done through the distribution of questionnaires. The analysis technique used is the method of PLS (Partial Least Square) analysis with SmartPLS 3.0 software. The results of this study indicate that (1) Brand Image has no significant effect on purchasing decisions with a path coefficient of 0.033. (2) Service Quality has a significant influence on purchasing decisions with a path coefficient of 0.743. (3) Prices have a significant influence on purchasing decisions with a path coefficient of 0.321. The highest contribution is in the influence of service quality on purchasing decisions with a path coefficient of 0.743